From Qur’anic Values to Entrepreneurial Impact: Field-Based Case Studies of Islamic MSMEs in Indonesia and Nigeria - Sarasi, Vita; Fadillah, Afrizal; Anwar, Khairul; Abdullahi, Nazifi Dahiru; Setiono, Muhammad Fahri; Aswandari, Desi (ZAD Al-Mufassirin, 2025)
This study explores the application of Qur’anic values in entrepreneurial practices and their implications for micro and small enterprises (MSMEs) in Indonesia and Nigeria. Using a qualitative field-based approach supported by library research, five institutions were examined: KOMIDA, Pesantren Daarut Tauhiid, Warteg Syariah, Kampung Marketer, and Jaiz Bank. Findings show that values such as ṣidq (honesty), ʿadl (justice), amanah (responsibility), taʿāwun (mutual assistance), prohibition of riba, and pursuit of barakah are operationalized through mechanisms including interest-free microfinance, group accountability, transparent pricing, faith-based entrepreneurship education, and inclusive institutional financing. In Indonesia, these practices foster trust, solidarity, and sustainability among MSMEs, while in Nigeria, Jaiz Bank demonstrates institutional commitment by expanding sector-specific support. The study’s novelty lies in bridging normative Qur’anic ethics with cross-country empirical evidence, positioning Islamic entrepreneurship as an alternative development paradigm balancing profitability, sustainability, and spiritual accountability. The comparison specifically focuses on dialectics of applying Qur’anic values across different ecosystem dimensions in two distinct context. Practical recommendations include: 1) embedding Qur’anic ethics in entrepreneurship education, SME training, and halal branding and 2) emphasizing policy reforms such as zakat and waqf digitalization, Islamic microfinance strengthening, and aligning regulation with maqāṣid al-sharīʿah. These insights highlight the transformative potential of Qur’anic values in shaping ethical, inclusive, and resilient economic ecosystems.